Ready or Not, It Will Come: Preparing Accountancy for the Next Disruption - Walters, Lisa M.; Hall, Linda A.; Grigsby, John D. (Journal of Applied Business and Economics, 2023)
This study investigates the atypical knowledge, skills, and abilities (KSAs) used by accounting practices during the 2020 U.S. income tax season amidst the COVID-19 pandemic shutdown. We hypothesize that many accountants found themselves serving in atypical roles and that most accounting firms underestimated the pandemic’s impact, leaving them unprepared to meet the challenge, and that some firm characteristics influence their state of preparedness. We emailed surveys to small, medium, and large accounting firms to investigate these hypotheses. We found that accounting firms used atypical KSAs significantly more often in 2020 than in previous years and that firms found these KSAs critical to their operations. Roughly 80% reported underestimating the impact of COVID-19. While firm size did not play a role in the usage of the KSAs we identified, there were differences in what firms rated highly important and easy to attain. We feel that these KSAs should be considered for ongoing professional development and in accounting curricula to support the sustainability of accounting practices in the face of future disruptions.